Emerging hemispheric asymmetry of Earth’s radiation - Norman G. Loeb; Tyler J. Thorsen; Seiji Kato; Fred G. Rose; Øivind Hodnebrog; Gunnar Myhre (Proceedings of the National Academy of Sciences, 2025)
Twenty-four years of satellite observations from the Clouds and the Earth’s Radiant Energy System show a northern hemisphere (NH) minus southern hemisphere (SH) trend difference of 0.34 ± 0.23 Wm −2 dec −1 (5 to 95% CI) in absorbed solar radiation (ASR) and a weaker trend difference of 0.21 ± 0.21 Wm −2 dec −1 in outgoing longwave radiation. The emerging darkening of the NH relative to the SH is associated with changes in hemispheric differences in aerosol–radiation interactions, surface albedo, and water vapor changes. Cloud changes also contribute to a greater ASR hemispheric contrast, but the magnitude is small due to opposing trend differences in the tropics and extratropics. The break in hemispheric symmetry in ASR challenges the notion that clouds naturally compensate for forced hemispheric asymmetries in noncloud properties. Hemispheric (a)symmetry in radiation is linked with the atmosphere–ocean general circulation. How clouds respond to this hemispheric imbalance has important implications for future climate.